Corrosion behaviour of austenitic and duplex stainless steels in an industrial strongly acidic solution. Issue 8 (8th December 2015) - Bellezze, T.; Giuliani, G.; Roventi, G.; Fratesi, R.; Andreatta, F.; Fedrizzi, L.
Abstract : AISI 316L metallic components of an industrial plant, producing tartaric acid as by‐product of grape pressing, were subjected to a so severe corrosive attack to promote the search of alternative stainless steels for this specific application. The aggressive industrial solution is strongly acidic and it contains large amounts of chlorides and sulphates and it operates in the temperature range of 25–60 °C. As possible alternative materials to AISI 316L, two super austenitic stainless steels, AISI 904L and Sanicro TM 28, and three duplex stainless steels, SAF 2707 HD TM, SAF 2507 TM and SAF 2205 TM, were tested. The steels were characterised by means of chemical analysis, metallographic observations and anodic polarisations in a tartaric acid saturated solution, both in presence and in absence of chlorides and sulphates. The AISI 316L alloy showed the presence of ferrite δ at the austenitic grain boundaries, which is responsible for a selective attack and severe damage of this material. Among the tested steels, as alternative to AISI 316L, Sanicro 28 TM and AISI 904L can be considered promising, with a preference for Sanicro 28 TM . SAF 2707 HD TM showed a passive behaviour only with a mirror surface finishing, which is not acceptable for service conditions. Abstract : Electrochemical tests have shown the best corrosion behaviour of the austenitic alloy Sanicro TM 28 which can replace AISI 316L, when used in industrial acidic solutions. Also SAF 2707 HD TM resulted in a promising alloy thanks to its pure passive behaviour, even at high temperatures. Nevertheless, this alloy showed an active and a selective corrosion when its surface roughness has been increased.